A study on the attributes involved in the hedonic pricing of Brazilian clothing. Issue 1 (1st January 2019) - Mandotti, Elaine; Felisoni De Angelo, Claudio; Bergmann, Daniel; Fouto, Nuno Manoel Martins Dias; Ferreira Savoia, José Roberto
ABSTRACT: The objective of this study is to identify the weighted importance of intrinsic and extrinsic attributes. Intrinsic attributes are defined as the specific features of products. Extrinsic attributes refer to other characteristics that are also important for price composition, such as brand, store layout and services, and purchasing experiences. In a survey with 1, 923 collected responses, it was possible to identify and quantify intrinsic and extrinsic influencing factors beyond price strategy in the Brazilian fashion market for blue jeans. The statistical analysis was based on the hedonic price method. The idea of expressing the price based on a series of intrinsic and extrinsic variables avoids the problem of using the regression technique. In this research, multiple linear regression and quantile regression were applied. The results show that extrinsic attributes have greater influence than intrinsic features on explaining the final market prices using log-linear and quantile regression statistical methods.